2008
DOI: 10.1002/tox.20360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cypermethrin, propetamphos, and combination involving cypermethrin and propetamphos on lipid peroxidation in mice

Abstract: Insecticides are the chemicals widely used in agriculture, environmental health, human-and animal-health fields. Exposure to insecticides has been associated with many hazardous effects, including antioxidative metabolism. In the current study, the effect of cypermethrin (CYP), propetamphos (PRO) and their mixtures on oxidative stress in mice to understand the possible health effects to animals and human beings was investigated. In the present study, 245 male Albino mice weighing 35-40 g were used. The mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 25 publications
4
19
0
1
Order By: Relevance
“…So, the decrease in the activity of SOD, CAT, and GST in prallethrin-intoxicated animals indicates insufficient detoxification of prallethrin in rats. The decline of antioxidant enzymes activity, in our study, supported earlier findings [68, 69] which demonstrated that exposure of rats to pyrethroids decreased antioxidant enzymes activity. The increment in lipid peroxidation, as assessed by the elevated levels of TBARS following insecticides administration, has been well documented [16, 19, 29, 59, 70, 71].…”
Section: Discussionsupporting
confidence: 92%
“…So, the decrease in the activity of SOD, CAT, and GST in prallethrin-intoxicated animals indicates insufficient detoxification of prallethrin in rats. The decline of antioxidant enzymes activity, in our study, supported earlier findings [68, 69] which demonstrated that exposure of rats to pyrethroids decreased antioxidant enzymes activity. The increment in lipid peroxidation, as assessed by the elevated levels of TBARS following insecticides administration, has been well documented [16, 19, 29, 59, 70, 71].…”
Section: Discussionsupporting
confidence: 92%
“…Kanbur et al [37] declared that propetamphos significantly increased the NO and other lipid peroxidation parameters in mice when given in the diet for 60 days. In this study the NO level in the aorta and the plasma was also increased in group given chlorpyrifos.…”
Section: Discussionmentioning
confidence: 99%
“…In the chronic toxicity trial, again the control group was administered with soy oil alone, whilst groups 2b, 3b, and 4b were administered daily with 12 mg/kg.bw of cypermethrin, 4 mg/kg.bw of propetamphos, and 12 mg/kg.bw of cypermethrin combined with 4 mg/kg.bw of propetamphos, respectively, in soy oil, by gavage directly into the stomach for a period of 60 days. The oral LD 50 values of both pesticides in rats (Ensley, ; Gupta and Milatovic, ), as well as the data obtained and doses administered in previous acute and chronic toxicity research carried out in rats and other experimental animals were used to determine the administration doses of cypermethrin (Eraslan et al, ; Kanbur et al, ) and propetamphos (Kanbur et al, ) used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Products resulting from its metabolism by microsomal enzymes are involved in its toxic mechanisms (Vittozzi et al, ; Garfitt et al, ; Kazemi et al, ) and eliminated largely in urine (Garfitt et al, ). Propetamphos is another pesticide known to cause oxidative stress (Kanbur et al, ). Thus, it leads to adverse effects in many tissues, organs, and systems (Garfitt et al, ; Kanbur et al, ; Cetin et al, ).…”
Section: Introductionmentioning
confidence: 99%